Developing Khuluqin 'Adzim Through Tarbiyah Yaumiyah Program - Hasnahwati; Syamsuddin, Sri Devi; Firmansyah, Eka (LETIGES, 2025)
This study analyzes tarbiyah yaumiyah program implementation strategies in developing khuluqin 'adzim among students at SMP IT Insan Madani Palopo, addressing the need for systematic Islamic character education models. Qualitative research using Yin's single case study design with participatory observation, in-depth interviews with the principal, two teachers, and six students, plus curriculum documentation analysis. Data analyzed using Miles, Huberman, and Saldaña's interactive model with triangulation validation. The implementation strategy includes differentiated methods, a tiered halaqah system with 21 Qur'an teachers, 3 juz memorization targets spanning over 3 years, and multi-level evaluation from tashih to public munaqasyah. The tarbiyah yaumiyah program effectively transformed student character through systematic spiritual habituation, showing concrete behavioral improvements in worship consistency, adab enhancement, and increased independence. Research contributes three theoretical concepts: